Training of Tutors in Problem Based Learning: Feedback of Participants - Thapa, Bindu; Soti, Harikala; Paudel, Sabita; Shrestha, Bijayata; Subedi, Nuwadatta; Piryani, Rano Mal (Journal of College of Medical Sciences-Nepal, 2024)
Background The faculty members should have knowledge on PBL process and must be familiar with the changing role of teacher to facilitator to adopt PBL as a teaching/learning strategy. The transition from the role of teacher to tutor is critical for the success of PBL. The objective of this study was to describe the process of proceedings of training workshop at the outset of introduction of PBL in Gandaki Medical College Nepal and assess the feedback of the tutors towards PBL training workshop. Methods Two one-day training workshops were organized at GMC; first on November 28, 2021, and second on October 16, 2022. Feedback of the participants was taken on valid semi-structured self-administered questionnaire at the end of proceedings of training workshops. Data was analyzed for frequency and central tendency. Results The response rate was 100% (Total number of participants =37). The training workshops were rated for usefulness (7.89±0.90), content (7.83±0.76), relevance (7.83±0.98), facilitation (7.91±1.11) and overall process (8.13±0.82) using scale 1-10(1=Poor, 10= Excellent). Most of the participants found the sessions moderately important ("PBL Process" 70.3%, "Role of Tutor" 75.7%, "Designing PBL problem package" 48.6%, and “Conducting PBL" 70.3%). The majority of the participants recommended increasing the duration of workshop, allocate adequate time for the practice session and arrange other types of training workshops in medical education. Conclusions The significance of PBL trainings was recognized by the participants. Overall, their feedback on training workshops were positive.